Kortejärvi Veiki moraine plateau - a key to the glacial history of northern Sweden - Lindqvist, Mimmi Adina (UiT Norges arktiske universitet, 2020)
In many parts of Scandinavia, the glacial history is more well established than in northern Sweden. The Veiki moraines in northeastern Sweden presumably store information about the Weichselian glaciations. The moraines were formed when stagnant ice was slowly melting under a thick debris cover, forming water filled sinkholes, that were left as elevated ice-walled lake plains when the ice finally melted. The latest age estimations of the Veiki moraines suggest that the landscape was formed during a Middle Weichselian interstadial. The late Weichselian ice sheet that covered much of northern Europe was presumably partially cold based and left the Veiki moraines nearly untouched. However, the age of the moraines had previously been suggested to be Early Weichselian and therefore possibly overridden by two consequent ice sheets. To this day, the ages of the moraines have been disputed. The highly irregular shapes of the moraines have caused some obscurity in the genesis of the Veiki moraines and in this report, subsequent processes are suggested as contributory factors in the formation of the landscape. The obtained OSL ages reinforce that the Veiki moraines were formed during a Middle Weichselian interstadial. The most prominent moraine plateaus were formed in well insulated parts of the ice where the debris cover was thick, while the less prominent moraine plateaus were in poorly insulated parts of the ice. The poorly insulated lakes were affected by faster melting rates and consequently they merged with surrounding lakes, forming a landscape of highly irregular merged ice-walled lake plains once the ice melted. A faster melting rate likely caused differences in the ice surface gradient and led to collapsing lakes in the downslopes. The landscape was later only slightly reworked by the Late Weichselian ice. Reworking by later fluvial processes makes the reconstruction of the original ice-walled lakes somewhat challenging. A geomorphologically unique Veiki moraine plateau has been studied using sedimentological and ...